PENGARUH PENERAPAN PROBLEM BASED LEARNING DENGAN TEKNIK MIND MAPPING TERHADAP HASIL BELAJAR BIOLOGI PESERTA DIDIK - Saparuddin; Dian Dwi Putri Ulan Sari Patongai; Sahribulan (Jurnal Biogenerasi, 2021)
This study aimed to determined the influence of problem based learning model with mind mapping techniques toward the biology learning outcomes. This study was a pre- experimental reasearch with one group pretest - posttest design. The sample of study consisted of one class is a class XI IPA9 SMAN 1 Sungguminasa as 50 students. Sample was take with a random sampling technique. The research instrument is learning outcome test in biological material (excretory system) with multiple choice shaped. Data were analyzed by employing inferential test (paired samples). The result of inferential analysis indicated that tcount 46.682>ttable 1.68, H0 was rejected, meaning that there was influence of problem based learning model by employing mind mapping technique toward students’ learning result.